Modulation of Schlemm’s Canal Endothelial Cell Stiffness via Latrunculin Loaded Block Copolymer Micelles - Stack, Trevor (J Biomed Mater Res A, 2018)
Increased stiffness of Schlemm’s canal endothelial cells (SC cells) is a major contributing factor to the increased pressure characteristic of primary open-angle glaucoma. New treatments for glaucoma are being developed using actin depolymerizers and rho kinase inhibitors to address this increased stiffness. However, these agents have off-target effects and are not as potent as had been hoped. We have developed a micellar nanocarrier assembled from poly(ethylene glycol)-bl-poly(propylene sulfide) copolymers capable of encapsulating latrunculin A (Lat A) with the goal of modulating SC cell stiffness. Lat A-loaded nanocarriers were similar in size and morphology to unloaded PEG-bl-PPS micelles, loaded Lat A at 62% encapsulation efficiency, and retained loaded Lat A for at least 22 days. The continued functional activity of Lat A following encapsulation within micelles was verified in murine macrophages, which are known to display decreased endocytosis in response to Lat A-dependent cytoskeletal disruption. Endocytic inhibition remained unchanged when comparing equal concentrations of micelle-loaded versus free form Lat A. Uptake of Lat A-loaded micelles by human SC cells was verified in vitro with no sign of cytotoxicity, and modulation of SC cell stiffness was measured by atomic force microscopy. Lat A-loaded micelles significantly decreased SC cell stiffness, which resulted in visible changes in cell morphology as observed by confocal microscopy. Our results demonstrate that PEG-bl-PPS micelles represent a tunable platform for the controlled intracellular delivery of latrunculin. These self-assembled polymeric nanobiomaterials may support the rational design and engineering of delivery systems for the treatment of glaucoma.